Penerapan Model Pembelajaran Berbasis Proyek dalam Kurikulum Merdeka untuk PAUD - Siti Nur Syarifah; Amanullah, Akhmad Syah Roni; Rachma, Zaskia Salsabilla (Institut Agama Islam Tarbiyatut Tholabah, 2023)
Project-based learning aligns with the idea introduced by John Dewey, acknowledging that children can construct their own knowledge through a structured learning process in the form of projects. Currently, the project-based learning model has become an integral part of the independent curriculum, closely related to the concept of independent learning to provide flexibility for learners. The purpose of this article is to intricately discuss how project-based learning is implemented, particularly at the early childhood education level. This research utilizes a descriptive qualitative approach with literature review as the data collection method. The research findings indicate that the concept of project-based learning is one of the models that supports the